Comparing mental health status and COVID‐19 event impact between survivors and the general population during the second wave of the pandemic in Iran - Maryam Hasannezhad Reskati; Motahareh Kheradmand; Mahmood Moosazadeh; Touraj Assadi; Misagh Shafizad; Akbar Hedayatizadeh‐Omran; Seyed Hamzeh Hosseini; Forouzan Elyasi (Wiley, 2023)
Abstract Background and Aim The coronavirus disease 2019 (COVID‐19) pandemic has to date overwhelmed the survivors and the general population. The present study aimed to compare the mental health status and the COVID‐19 event impact between the survivors and the general population in Mazandaran Province, Northern Iran. Design A web‐based cross‐sectional survey was used. Methods This study was performed using convenience sampling. Results In total, 1,766 participants were included in this study. The findings revealed that the posttraumatic stress disorder (PTSD) severity in both outpatient and hospitalized groups was significantly higher than that in the general population. Besides, the levels of anxiety and depression in the group receiving inpatient care and treatment had significantly elevated than those in the general population. Conclusion Given the high prevalence rate of mental disorders, healthcare professionals are recommended to plan for various interventions and support services to boost community mental health status.